Grapevine Wood-Degrading Activity of Fomitiporia mediterranea M. Fisch.: A Focus on the Enzymatic Pathway Regulation - Pacetti, Andrea; Moretti, Samuele; Perrin, Célia; Gelhaye, Eric; Bieler, Evi; Kassemeyer, Hanns-Heinz; Mugnai, Laura; Farine, Sibylle; Bertsch, Christophe (Frontiers in Microbiology, 2022)
Fomitiporia mediterranea is a Basidiomycota fungus associated with some of the Esca complex diseases and responsible for decay in grapevine wood. Its role in the onset of foliar symptoms has recently been reconsidered, mainly after evidence showing a reduction in foliar symptom expression after rotten removal of wood. The study of its degradation pathways has already been approached by other authors and with this study much information is consolidated. Microscopic observation of degraded wood provides a first approach to the characterization of F. mediterranea modalities of wood cellular structure degradation. The decay of grapevine wood was reproduced in vitro and the measurement of each wood-forming polymer loss highlighted characteristics of F. mediterranea common to selective white rot and showed how fungal strain and vine variety are factors determining the wood degradation. All these observations were supported by the analysis of the laccase and manganese peroxidase enzyme activity, as well as by the expression of the genes coding 6 putative laccase isoforms and 3 manganese peroxidase isoforms, thereby higlighting substantial intraspecific variability.